A Decade of JFM in India : Looking Back for better foresight - Kumar, Ajay (Indian Forester, 2000)
Joint Forest Management (JFM) is a strategy in the right direction for decentralised people-oriented forestry management in India. It is also a process for empowering the people and strengthening democracy. However, the need of the hour is to analyse the ground realities and then take a decision to make the JFM programme a long term sustainable movement. The basic problems should be reviewed and a new approach is to be made, putting economic parameters at the top of the agenda. A few strategies like categorising, zoning of areas, precise sharing of benefits, etc. need to be chalked out. JFM is not like a wide-spectrum antibiotic drug to cure many ills at a time. Rather, it is a symptom specific specialised medicine to be prescribed with due care and caution.